Available evidence for mosquito-borne Francisella tularensis transmission is inconclusive - Jonckers Nieboer, L. F. W.; Fischer, E. A. J.; Braks, M. A. H. (Frontiers in Tropical Diseases, 2023)
Various arthropod vectors are responsible for the transmission of pathogens that cause serious diseases in humans. Some important pathogens are transmitted by mosquitoes during blood-feeding, for example the well-known parasite causing malaria, and viruses-causing diseases such as dengue, chikungunya, and Zika virus fever. In contrast, very little is known about the potential of mosquitoes to transmit pathogenic bacteria. Hitherto, only a few bacteria have occasionally been suggested to be spread by mosquitoes, but this is not widely known nor accepted, and literature on this topic is limited. The aim of this study was to review the literature about the possible role of mosquitoes in the transmission of the bacterium F. tularensis, the causal agent of tularaemia, which has been proposed by several experts. Available primary articles investigating this possible vector role of mosquitoes were analysed and evaluated based on four vector incrimination criteria. This demonstrated that several studies had indeed found indications of a correlation between mosquito bites and tularaemia, and that the results of some other studies suggested that such a vector role for mosquitoes might exist. However, conclusive evidence of a causal relationship was not found, nor irrefutable proof that mosquitoes can actually transmit this bacterium during blood-feeding. This literature review has provided an overview of the current relevant literature, shows that future studies should focus on gaining more insight into other explanations for the correlation between mosquito bites and tularaemia, and that the certainty with which some authors write about the vector role of mosquitoes is not entirely justified.